The Effect of Marketing Mix on Consumer Loyalty of Telkomsel Internet Card (Case Study on University Faculty of Economics South Sumatra) - Agus Salim (Journal of Indonesian Management, 2022)
The quality of service in the price provided through Telkomsel products is by providing a nominal recharge of pulses from five thousand rupiah to millions of rupiah, this is intended to provide many choices to consumers so that the nominal price of Telkomsel top up pulses is affordable by all layers. The internet packages that Telkomsel offers to the public include Physical Internet Voucher Packages starting from 1.5 GB Packages up to 14 GB Packages, Telkomsel Halo Unlimited, Telkomsel Zoom Pro Packages, 5G Orbit Internet Packages, Telkomsel Prepaid Combo Sakti Packages, OMG Prepaid Telkomsel Packages ! Watch , Telkomsel Prepaid Kuota Ketengan Package, Telkomsel Prepaid Kuota Family Package. The research method is a scientific way to obtain data with a specific purpose and use. The method used in this study is a quantitative method so that the data in this study is quantitative data. Quantitative data is data in the form of numbers, such as data measuring intervals and ratios (Darmadi, 2001:19). In terms of the methods and techniques of data collection, the data collection techniques can be done by interview (interview), questionnaire (questionnaire), Observation (observation) and a combination of the three. The analysis used to determine the effect of several independent variables X with one dependent variable Y, which is expressed by the multiple regression formula. Based on the results of data analysis through the help of the SPSS program regarding the influence of the marketing mix on Telkomsel internet card consumer loyalty, the following conclusions can be drawn: From the results of multiple linear regression tests. It was found that the most dominant marketing mix variable was the distribution variable of 0.238, followed by the product variable of 0.214, the price variable of 0.161 and the last variable of promotion was 0.150.